Moderating Effect of Chief Executive Officer Narcissism in the Relationship Between Corporate Social Responsibility and Green Technology Innovation - Yang, Hailan; Shi, Xiangjiao; Wang, Shuo (Frontiers in Psychology, 2021)
This study focuses on the impact of corporate social responsibility (CSR) on green technology innovation (GTI) of firms and moderating influence of CEO narcissism through the lens of stakeholder theory and upper echelons theory. This research deconstructs CSR into internal CSR and external CSR in order to reveal the effects of different types of CSR on GTI. Based on a sample of 1,745 firm-year observations from 349 Chinese listed firms across sectors between 2014 and 2018, we find the fulfillment of internal CSR has a significant positive impact on GT. This relationship is strengthened when the CEOs are narcissistic. The external CSR has a significant negative impact on GTI and this relationship is strengthened by CEO narcissism. The major contribution of our study is that it provides a theoretical contribution to the existing literature by deconstructing CSR into internal and external CSR and enriches the studies in the context of CSR from a point of view of CEOs’ particular personality trait.